Visual Pleasure New Media (Analisis Semiotika Male Gaze pada Akun Tiktok @Goodponselangels) - Amanda Amalia Faustine Gittawati (Communications, 2023)
This study aims to analyze the forms of Male Gaze that are displayed in a series of content presented by the Tiktok account @Goodponselangels which is an alternative account from the previous account, namely @Goodponsels. This account is presented for none other than supporting promotion, by focusing on content that focuses on the popularity of the Good Ponsel team, the Good Angels. Visual Pleasure does not stop at conventional media but is also found in new media such as Tiktok which is now popular for many people. Tiktok has become a very profitable promotional alternative with various efforts, one of which is by presenting the visual enjoyment of the female body for Tiktok users. This study uses a qualitative approach with the semiotic analysis of the character Roland Barthes who examines three sign maps namely denotative, connotative and myth formed by the accounts of good angels. The results of the study show that the denotative signs generated by the tiktok account @Goodponselangels are in the form of movement, use of clothing, and audio as a map. Taking pictures and expressions that are shown while swaying in content following audio that is currently popular contains a connotative meaning that represents male gaze and makes the woman a sensual passive object that is attractive and gives visual satisfaction to the audience, thereby forming a myth that this is a which is reasonable and is a form of freedom of expression, which without realizing it is a form of threat to women.